Prevalence of Post-Traumatic Stress Disorder and Associated Factors Among Internally Displaced Persons (IDPS) In Mogadishu Cross-Sectional Study - Sh Abukar IM; Asir Rage AA; Warsame MO (Psychology Research and Behavior Management)
Ismail Mohamed Sh Abukar,1 Abdirashid Ali Asir Rage,1 Mohamed Omar Warsame2 1School of Public Health and Research, Somali National University, Mogadishu, Somalia; 2Department of Public Health, Federal Ministry of Health and Human Services, Mogadishu, SomaliaCorrespondence: Mohamed Omar Warsame, Email diirshe143@gmail.comBackground: An important mental health concern is Post-Traumatic Stress Disorder (PTSD), especially for Internally Displaced Persons (IDPs) in the Horn of Africa. Limited access to psychosocial support and primary health care exacerbates mental health issues.Aim: This study was to examine the prevalence of post-traumatic stress disorder and factors associated with IDPs in Mogadishu.Methods: A cross-sectional study was conducted from Sep 25 to Oct 20, 2023, employing analytical design. The study population included individuals aged 18 and older directly exposed to forced displacement due to conflicts and disasters. A multistage random sampling method was used, with a final sample size of 364 participants from over 20 different camps in Daynile and KAHDA. Post-Traumatic Stress Disorder (PTSD) was assessed using Questionnaire of Post-Traumatic Stress Disorder Checklist for DSM-5 (PCL-5).Results: The prevalence of PTSD among participants was 60%. The PTSD prevalence was highest among male respondents at 75% compared to 54% among the females with over half (63%) of the PTSD cases being females, while 37% were males. Only 0.3% reported the availability of mental health services, emphasizing the lack of adequate support.Conclusion: The study highlights a significant prevalence of PTSD among Mogadishu’s IDPs, underscoring the immediate need for mental health prioritization to address challenges in conflict-affected areas. The lack of mental health integration into primary care requires urgent intervention for enhanced services in the Horn of Africa. Recommendations propose targeted mental health interventions, especially for females, addressing gender-based violence and loss. Programs should consider those with multiple displacements, addressing cumulative trauma impact. Providing comprehensive support for those facing property destruction is crucial. Collaborative efforts among humanitarian organizations, local authorities, and mental health professionals are vital for an effective response to the mental health challenges faced by IDPs in conflict-affected areas.Keywords: prevalence, post-traumatic, stress disorder, factors and internal displaced persons